Transient analysis of mechanically switched capacitor with damping network - Adel Mohamed, Saleh Handi
Mechanically switched capacitor with damping network (MSCDN) is used as reactive power compensation unit in the modern power systems. MSCDN stabilizes the voltage and increases the transmission capacity to ensure the availability of reactive power for feeding in the injection of reactive power at short notice. The transient overvoltage phenomenon often occurs in MSCDN due to the lightning surge, switching surge, fault, resonance, circuit breaker operation, etc. These transients impose great stresses to the MSCDN and its components and could lead to insulation breakdown, discharge, flashover, explosion, and so on. For this reason, studying the overvoltage of power system is of extreme importance. In this thesis, the studied MSCDN consists of a main capacitor (4.54 μF) supplying the desired amount of reactive power (225 MVar) at a nominal voltage of 400 kV, connected to damping network providing sufficient damping of switching processes. The damping network consists of an auxiliary capacitor (35.81μF), damping resistor (474.07 Ω) and a filter reactor (282.94 mH). The main aim of this study is to determine transient voltages and currents for single and three phase’s system and find the ideal switching condition that gives the lowest overvoltage magnitude at each MSCDN components. In this work, the transient stresses of MSCDN components were determined by varying the closing and opening times of the circuit breaker for both single and three-phase connections. Variations in the circuit breaker times simulate the synchronous switching conditions of the MSCDN. For the single-phase analysis, analytical calculation using Laplace transform was used to calculate the transient currents and voltages, and the results obtained were compared with ATP simulation for validation. Alternative Transient Program (ATP-EMTP) was employed to reproduce the switching operation of MSCDN, as ATP gives solution in time domain and very useful for comparisons with analytical method conducted in this work. For single phase, it was found that the ideal switching cases were obtained when switching at 0 and 5 ms respectively. Furthermore, for three-phase MSCDN, the energisation and de-energisation of MSCDN were simulated to identify the transient voltages and currents for synchronous switching. Based on the results obtained, the ideal synchronous closing time of all phases was 5 ms. For MSCDN de-energisation studies, the simulation results obtained showed that there are no visible transients produced by synchronous de-energisation of MSCDN. This is the advantage of MSCDN circuit as compared to regular capacitor banks.